(untitled) (JOURNAL OF BAJA HEALTH SCIENCE, 2025)
The Setabelan Community Health Center has not implemented the SIMPUS application optimally because the internet network is unstable, there are still new employees who have not received socialization regarding the use of the SIMPUS application, and online patient registration has not been opened because the community is still unfamiliar with technology. Analyzing how effective the acceptance of the use of the SIMPUS (Community Health Center Management Information System) application is using the TAM (Technology Acceptance Model) theory at the Setabelan Health Center in Surakarta City. This type of research is qualitative and descriptive with data collection methods in-depth interviews with 11 informants including SIMPUS coordinators, SIMPUS programmers, nurses, midwives, pharmacists, dental nurses and administrative staff. The sample selection method used purposive sampling method. Using the SIMPUS application is useful for facilitating and speeding up health services and providing accurate data and information for decision making. There needs to be increased supervision and training of medical personnel in using the SIMPUS application. The use of the SIMPUS application is considered effective in the report submitted to the Surakarta City Health Service, however improvements to the interface and usability are still needed to make the application more attractive and easy to understand for all users and It is necessary to evaluate and develop applications periodically.